Sometimes, it doesn't figure - Abd Razak, Dzulkifli (2005)
THERE is a popular saying among statisticians which goes like this: Lies, damned lies and statistics! It may sound weird coming from statisticians them selves, but it is a recognition that statistics are not to be relied upon completely. There are too many things that can be buried under statistics. Ask any statistician. So it was a great relief to read a clarification in the Dewan Rakyat last week on reports that 80,000 graduates were unemployed. Minister in the Prime Minister's Department Datuk Mustapa Mohamed has put the record straight, though to some extent the damage has already been done. As expected, it all boiled down to how the statistics are compiled or constructed. In this case, it was a simple case of (mis)understanding of what the category "graduate" stands for.